Morphology of the Testis and Epididymis of Large White Boars - Samuel Gbadebo Olukole; Bankole Olusiji Oke (Turkish Journal of Agriculture: Food Science and Technology)
The testis and epididymis of twenty five adult Large White boars were used to investigate the biometric and histomorphometric parameters of the testis and epididymis of the boars. The aim of the study was to provide information which could be useful in the comparative regional anatomy of the male reproductive organs of domestic animals and thus an improved assessment of breeding soundness and fertility potential in boars. The average weight of the animals was 71.3 ± 10.7 kg. The average weights of the right and left testes were 170 ± 0.7.60 g and 179±6.48g, respectively with no significant dif¬ference. The average weights of the right and left epididymis were 40.9 ± 6.81 g and 43.7 ± 8.55 g, respectively, with no significant difference. The relative testicular and epididymal weights were 0.49% and 0.12%, respectively. This study shows that the testis is about four times the size of the epididymis. The ductal diameter of the head, body and tail of the epididymis were 418 ± 22.6 µm, 432 ± 20.3 µm and 939 ± 50.6 µm, respectively. The mean relative volume of the germinal epithelium, interstitium and lumen of the seminiferous tubules of the boars rats were 68.4 ± 3.46%, 5.5 ± 0.66% and 78.0 ± 4.81%, respectively. It can be concluded that the morphology of the testis and epididymis of the Large White boar are similar to those of most mammals. This work provides information the testis and epididymis of the Large White boar which could be useful in the comparative regional anatomy of the male reproductive organs of domestic animals and thus an improved assessment of breeding soundness and fertility potential in boars.